Fabrication, Properties, and Performance of Polymer-Clay Nanocomposites for Organic Dye Removal from Aqueous Media - Yao Mawuena Tsekpo; Augustine Nana Sekyi Appiah; Lucas Nana Wiredu Damoah; Daniel Amusah; Ebenezer Annan (Adsorption Science & Technology)
Methylene blue dye (MB dye) is a harmful contaminant for wastewater streams of industries and is harmful to human and aquatic life. An ecofriendly sugar templating process was used to generate porous bentonite/polydimethylsiloxane (PB) and porous magnetite nanoparticles/bentonite/polydimethylsiloxane (PBNP) composite absorbents to remove MB dye in this study. During the infiltration of PDMS solution into the sugar template in the vacuum chamber, bentonite and magnetite particles were integrated on the surface of the PDMS, and the porous structure was generated during the leaching out of sugar particles in water. The absorbents were characterized using Fourier infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The absence of the methyl bond at 2924 cm-1 and phenol bond at 3325 cm-1 in the FTIR spectra of the formed membrane proves that the food grade sugar was completely removed. The SEM images confirm that porosity was achieved as well as uniform mixing of the in the formation of composite. MB dye was effectively removed from wastewater using the as-prepared composite as absorbent. The removal efficiencies of the composite PBNP and PB were ~91% and ~85%, respectively. The experimental data was applied to pseudo-first-order (PFO) and pseudo-second-order (PSO) kinetic models as well as the Dubinin-Radushkevich, Harkins-Jura, and Elovich models for the adsorption isotherm. The data was found to fit the pseudo-second-order and Elovich models, respectively. The results show that the presence of magnetite nanoparticles improved MB dye removal significantly.